Online Education during COVID-19 Pandemic: Challenges for Children with Disabilities - Farooq, Tania; Manzoor, Shazia (Indian Journal of Educational Technology, 2022)
The COVID-19 pandemic has hit hard every aspect of life and has affected everyone disproportionately. Due to its viral and contagious behaviour, it forced the closure of educational institutions including those working for children with disabilities. In Kashmir, the schools were closed in March, 2020 and were reopened for a very brief period in March 2021, following a subsequent lockdown in March 2021 only. Consequently, the educational institutions resorted to an online mode of education to avoid any academic losses for the students. While this decision seemed a viable option, the vulnerable groups like children with disabilities and children enrolled in special schools found it difficult to cope with this medium of education. This is particularly for students with visual disabilities, developmental disabilities and hearing and speech impairments. In this regard, this paper is an attempt to unravel the experiences of parents of this vulnerable group. We have followed a qualitative methodology and interviewed twenty parents of children with different disabilities to explore their experiences of the online mode of education and its implications for their children with disabilities.